Treatment components in behavioral versus nondirective telephone‐assisted self‐help interventions for parents of children with externalizing behavior problems. Issue 5 (24th September 2021) - Treier, Anne‐Katrin; Hautmann, Christopher; Katzmann, Josepha; Nordmann, Lisa; Pinior, Julia; Scholz, Kristin‐Katharina; Döpfner, Manfred
Abstract: Background: The aim of this study was to analyze treatment differentiation in a behavioral and a nondirective telephone‐assisted self‐help intervention for parents of children with externalizing behavior problems, including the development and evaluation of a rating scale. Methods: In a randomized controlled trial, 149 parents of children aged 4–11 years with externalizing behavior problems were allocated to a behavioral or a nondirective guided self‐help intervention. Parents in both conditions received eight self‐help booklets and ten telephone consultations. To analyze the content of the interventions, we developed the Therapist Intervention Scale (TIS). In order to evaluate the scale and analyze treatment differentiation, parent booklets and recorded telephone consultations were rated. Results: Item selection and scale development were based on predefined psychometric criteria. The subscales Guidance & Structures and Relationship & Emotions were developed based on exploratory factor analyses. Interrater reliability and internal consistency were found to be acceptable to excellent. Analyses of construct validity demonstrated positive correlations for corresponding and negative correlations for non‐corresponding subscales of therapist ratings. Therapists and booklets in the behavioral intervention showed higher scores on the subscale Guidance & Structures, while therapists and booklets in the nondirective intervention showed higher scores on the subscale Relationship & Emotions. Conclusion: The analyses of the TIS support its reliability and validity. The subscale Guidance & Structures contains mainly cognitive‐behavioral treatment components, while the subscale Relationship & Emotions contains mainly nondirective treatment components. The implemented telephone‐assisted self‐help interventions demonstrated distinct treatment profiles which match their intended therapeutic approaches.